IDDF2019-ABS-0222 Exchange transfusion in neonatal hyperbilirubinemia and bilirubin encephalopathy: a long way to go. (June 2019) - Jajoo, Mamta
Abstract : Background: Hyperbilirubinemia is the most common morbidity in neonates. Exchange transfusion (ECT) has an important role in the prevention of Bilirubin Encephalopathy in neonates. Aim: To evaluate the incidence and risk factors of Bilirubin Encephalopathy in neonates presenting with neonatal hyperbilirubemia requiring ECT. Subjects: All neonates admitted with hyperbilirubinemia requiring exchange transfusion. Methods: Retrospective study underwent exchange transfusion over a period of 30 months in a level III extramural Neonatal Intensive care Unit of Delhi. Demographic data, etiology of jaundice, the presence of encephalopathy, details of ECT and ECT-related adverse events were analyzed. Results: Total of 1675 neonates were admitted, out of which 136(8.1%) neonates underwent exchange transfusion. The mean(SD) gestational age and mean weight(SD) on admission were 36±3 weeks and 2144.5±678 gram respectively. The mean age of presentation was 5.48±3.9 days and the mean day on which jaundice appeared was 4.9±3.33 days. The mean bilirubin on presentation and duration of phototherapy were 24.2±5.8 mg/dl and 3.2±1.7 days respectively. Out of 136 neonates, 20(14.7%) were home delivered. Sepsis 49(36%) was the most common cause of NNH requiring ECT. Other causes were ABO incompatibility(21.3%), Rh incompatibility(11.7%), hypothyroidism(3.6%), G6PD deficiency(0.7%) and Idiopathic . Five (3.6%) neonates were blood culture positive. ECT through umbilical route was done in 115(84.5%) and through peripheral route in 21 (15.4%). More than one ECTs were required in 5(3.6%). The complications of ECT were hypocalcaemia (38.2%), thrombocytopenia (17.6%) and hypothermia (11%). Thirty-nine neonates (28.6%) had encephalopathy on admission; the mean day of presentation, weight and bilirubin in these neonates were 5.5±3.7 days, 2142.6±763 grams, 26.9±6.13 mg/dl respectively. Conclusions: The incidence of NNH developing Bilirubin encephalopathy is still very high in our country, most probably because of early discharge, loss to follow up and delay in diagnosis and treatment. Timely intervention and proper counseling of mother at the time of discharge after birth is very important to prevent encephalopathy in neonates with NNH